2005
DOI: 10.1002/jcp.20552
|View full text |Cite
|
Sign up to set email alerts
|

Four novel RUNX2 mutations including a splice donor site result in the cleidocranial dysplasia phenotype

Abstract: Cleidocranial dysplasia (CCD) is an autosomal dominant disorder caused by haploinsufficiency of the RUNX2 gene. In this study, we analyzed by direct sequencing RUNX2 mutations from eleven CCD patients. Four of seven mutations were novel: two nonsense mutations resulted in a translational stop at codon 50 (Q50X) and 112 (E112X); a missense mutation converted arginine to glycine at codon 131 (R131G); and an exon 1 splice donor site mutation (donor splice site GT/AT, IVS1 + 1G > A) at exon 1-intron junction resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 39 publications
3
59
1
2
Order By: Relevance
“…Furthermore, many in vitro studies have shown that Runx2 is a positive regulator for the expression of bone matrix genes, including type I collagen, osteopontin, bone sialoprotein, osteocalcin, and matrix metalloproteinase 9 (6-10). The heterozygous mutation of Runx2 results in cleidocranial dysplasia, a dominantly inherited developmental disorder of bone, in both mice and humans (3,4,(11)(12)(13). Moreover, Runx2 accelerates chondrocyte differentiation in response to the upregulation of Runx2 target genes, which include the indian hedgehog (Ihh) and type X collagen (Col10A1) (14,15).…”
Section: Function Of Runx2 and Estrogen In Bone Tissuesmentioning
confidence: 99%
“…Furthermore, many in vitro studies have shown that Runx2 is a positive regulator for the expression of bone matrix genes, including type I collagen, osteopontin, bone sialoprotein, osteocalcin, and matrix metalloproteinase 9 (6-10). The heterozygous mutation of Runx2 results in cleidocranial dysplasia, a dominantly inherited developmental disorder of bone, in both mice and humans (3,4,(11)(12)(13). Moreover, Runx2 accelerates chondrocyte differentiation in response to the upregulation of Runx2 target genes, which include the indian hedgehog (Ihh) and type X collagen (Col10A1) (14,15).…”
Section: Function Of Runx2 and Estrogen In Bone Tissuesmentioning
confidence: 99%
“…RUNX2 is also known as core binding factor A1 (CBFA1) and it is located on chromosome 6p21 (Bae et al, 1993;Ducy et al, 1997). It is generally believed that the haploinsufficiency or loss of function of RUNX2 underlies the mechanism of CCD pathogenesis (Quack et al, 1999;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous CCD patients without any detectable mutations in RUNX2 by sequencing or FISH have been identified (Kim et al 2006;Otto et al 2002;Quack et al 1999;Yoshida et al 2002). This would indicate a genetic heterogeneity such as mutation in RUNX2 gene's interacting proteins or regulatory elements or due to other mechanism that was not yet reported.…”
Section: Introductionmentioning
confidence: 99%